2019
DOI: 10.1111/adb.12736
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK‐dependent autophagy in the nucleus accumbens opposes cocaine‐induced behaviors of mice

Abstract: Cocaine is a strong central nervous system stimulant, which can induce drug addiction. Previous studies have reported that cocaine-induced autophagy is involved in neuroinflammation and cell death. However, the role of autophagy in psychomotor sensitivity to cocaine has not been explored. Here, we reported that D 1 receptor -CaMKII-AMPK-FoxO3a signaling pathway was involved in acute cocaine application-induced autophagy in the nucleus accumbens (NAc) both in vitro and in vivo. Furthermore, we found that knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Meanwhile, coordinating with mitochondria, ER stress induced by cocaine exposure via disrupting intracellular calcium homeostasis may also simultaneously induce apoptosis [ 57 , 58 ]. In addition, studies have suggested that autophagic cell death participates in the neurotoxicity of cocaine [ 59 , 60 ]. However, the role of cocaine-induced autophagy in neurotoxicity remains to be elucidated.…”
Section: The Neurotoxicity Of Cocainementioning
confidence: 99%
“…Meanwhile, coordinating with mitochondria, ER stress induced by cocaine exposure via disrupting intracellular calcium homeostasis may also simultaneously induce apoptosis [ 57 , 58 ]. In addition, studies have suggested that autophagic cell death participates in the neurotoxicity of cocaine [ 59 , 60 ]. However, the role of cocaine-induced autophagy in neurotoxicity remains to be elucidated.…”
Section: The Neurotoxicity Of Cocainementioning
confidence: 99%
“…In fact, autophagy grants the survival of both DA-and NE-containing neurons during a variety of stressful conditions (49,51,52,68,70). Autophagy alterations are associated with the effects of abused substances (amphetamine, methamphetamine, cocaine, ethanol) on brain catecholamine neurons concerning their morphology, neuroplasticity, as well as neurotoxic and behavioral effects (51,52,56,61). This is evident by a variety of behavioral effects produced by psychostimulants based on autophagy-dependent alterations (56,61).…”
Section: A Brief View Of the Autophagy Machinery: From Degradation Ofmentioning
confidence: 99%
“…Autophagy alterations are associated with the effects of abused substances (amphetamine, methamphetamine, cocaine, ethanol) on brain catecholamine neurons concerning their morphology, neuroplasticity, as well as neurotoxic and behavioral effects (51,52,56,61). This is evident by a variety of behavioral effects produced by psychostimulants based on autophagy-dependent alterations (56,61). Psychostimulants alter neuroplasticity of DA and NE neurons through receptor sensitization/desensitization while affecting their activity and metabolism (7,49).…”
Section: A Brief View Of the Autophagy Machinery: From Degradation Ofmentioning
confidence: 99%
See 2 more Smart Citations